3D Printed Sugar‐Sensing Hydrogels. Issue 9 (4th May 2020) - Bruen, Danielle; Delaney, Colm; Chung, Johnson; Ruberu, Kalani; Wallace, Gordon G.; Diamond, Dermot; Florea, Larisa
Abstract : Front Cover : In article 1900610, Gordon G. Wallace, Larisa Florea, and co‐workers fabricate 3D‐printed, sugar‐sensing hydrogels. When sugar molecules are introduced into the system, the hydrogel in contact with the sugar molecules appears fluorescent.